Tattoo ink induces inflammation in the draining lymph node and alters the immune response to vaccination - Arianna Capucetti; Juliana Falivene; Chiara Pizzichetti; Irene Latino; Luca Mazzucchelli; Vivien Schacht; Urs Hauri; Andrea Raimondi; Tommaso Virgilio; Alain Pulfer; Simone Mosole; Llorenç Grau-Roma; et al. (Proceedings of the National Academy of Sciences, 2025)
Despite safety concerns regarding the toxicity of tattoo ink, no studies have reported the consequences of tattooing on the immune response. In this work, we have characterized the transport and accumulation of different tattoo inks in the lymphatic system using a murine model. Upon quick lymphatic drainage, we observed that macrophages mainly capture the ink in the lymph node (LN). An initial inflammatory reaction at local and systemic levels follows ink capture. Notably, the inflammatory process is maintained over time, as we observed clear signs of inflammation in the draining LN 2 mo following tattooing. In addition, the capture of ink by macrophages was associated with the induction of apoptosis in both human and murine models. Furthermore, the ink accumulated in the LN altered the immune response against two different types of vaccines. On the one hand, we observed a reduced antibody response following vaccination with an messenger ribonucleic acid (mRNA)-based severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine, which was associated with a decreased expression of the spike protein in macrophages in the draining LN. In contrast, we observed an enhanced response when vaccinated with influenza vaccine inactivated by ultraviolet (UV) radiation. Considering the unstoppable trend of tattooing in the population, our results are crucial in informing the toxicology programs, policymakers, and the general public regarding the potential risk of the tattooing practice associated with an altered immune response.